Delayed release phosphatidylcholine in chronic-active ulcerative colitis: a randomized, double-blinded, dose finding study - Stremmel, Wolfgang; Gauss, Annika; Hanemann, Anja; Ehehalt, Robert; Autschbach, Frank; Karner, Max (Journal of clinical gastroenterology, 2010)
Background - In 2 preceding studies, delayed release phosphatidylcholine (rPC) was found to (a) improve disease activity and (b) withdraw steroids in patients with chronic-active ulcerative colitis. - Goal - Objective of the study was to determine the most effective rPC dose with least adverse events. - Study - A randomized, dose-controlled, double-blinded study. Four groups of 10 patients each with nonsteroid-treated, chronic-active ulcerative pancolitis with a clinical activity index (CAI) and endoscopic activity index (EAI) ≥7. Patients were treated with oral rPC at doses of 0.5, 1, 3, and 4 g daily over 12 weeks. - Results - The CAI changes from baseline to the end of the study were 2.5 (0.5 g), 7.0 (1 g), 5.5 (3 g), and 6.0 (4 g dose arm). Significant improvement of the CAI was registered between the lowest rPC dose of 0.5 g (control group) and all higher doses of 1.0, 3.0, and 4.0-g rPC (P≤0.05). Remission (CAI ≤3) was reached in 5/10 and 6/10 patients in the 3 and 4-g dose groups compared with no patients in the 0.5-g arm (P=0.033). In the 1-g dose group only 3/10 patients reached remission (P=0.21). The rates of clinical response (≥50% CAI improvement) were 70% in all of the effective dose groups (1 to 4 g, P=0.003). This was paralleled by the EAI improvement and by the rates of mucosal healing. Median time to clinical response was 5 (IQR 2 to 8) weeks. Bloating was registered in 40% of the patients irrespective of the treatment dose. Three of the 10 patients in the 4 g dose group reported nausea. - Conclusion - We found a saturable dose response of rPC in the treatment of chronic-active ulcerative colitis with effective doses ≥1 g per day; doses of 3 and 4 g seem to be superior in achieving remission.
Gesehen am 01.09.2023